Urban pest control a practioner's guide - Dhang, Partho (CABI, 2018)
This book, inclusive of 13 chapters, focuses on the control of invertebrate and vertebrate pests that commonly infest man-made structures. With emphasis on the most important pest organisms, specific chapters are devoted to the discussion of control strategies for cockroaches, flies, mosquitoes, bed bugs, termites, rats and mice, bats and birds. Chapters for the control of sporadic pests and pests of stored products are also included, as well as chapters for insecticide formulations, insecticide baits and baiting, and integrated pest management. The last chapter explores safety considerations in handling pesticides. With these contents, this book aims to be of valuable use to practitioners engaged in pest control services